Motivation for Using ICT and Pupils with Learning Difficulties - Lepičnik Vodopivec, Jurka; Bagon, Spela (International Journal of Emerging Technologies in Learning (iJET), 2016)
Teachers often consider modern active teaching methods to be better suited for students who are good at learning or even for gifted students, as they assume that students with learning disabilities have underdeveloped metacognitive and social learning skills, that they require more time to grasp the techniques of the more advanced, technology aided teaching methods and that they cannot acquire additional knowledge at the same time. Our research focuses on pupils with learning disabilities, their attitude towards learning and teaching with the help of ICT and on motivation that arises from it. The study has shown that students with learning disabilities are confident enough in their computer skills that teachers may freely use modern teaching methods with them in primary school, as even those children are motivated and have a good attitude towards such teaching methods.